Evaluation of Hindlimb Deformity and Posture in Dogs with Grade 2 Medial Patellar Luxation during Awake Computed Tomography Imaging while Standing - Tomo, Yuma; Edamura, Kazuya; Yamazaki, Atsushi; Tanegashima, Koji; Seki, Mamiko; Asano, Kazushi; Tinga, Selena; Hayashi, Kei (Veterinary and Comparative Orthopaedics and Traumatology, 2021)
Objective The aim of this study was to determine the degree of bone deformities and hindlimb postural abnormalities in a standing position in awake Toy poodles with and without grade 2 medial patellar luxation (MPL) using high speed 320-row computed tomography (CT).Methods The limbs with grade 2 MPL (MPL-G2 group) and without any orthopaedic disorders (control group) were imaged in a standing position, without sedation or anaesthesia, using CT. In MPL-G2 group, images were obtained when the patella was luxated (G2-L group) and reduced (non-luxation, G2-NL group). Bone morphologies of the femur and tibia were quantified three-dimensionally. Hindlimb standing posture was evaluated by measuring femoral rotation and abduction angles, tibial rotation angle, metatarsal rotation angle, foot rotation angle, angle between the femoral anatomical axis and the mechanical axis of hindlimb and stifle joint line convergence angle.Results There were no significant differences in bone morphologic parameters between the MPL-G2 group (5 limbs) and the control group (6 limbs). In the G2-NL group, there were no significant hindlimb postural abnormalities. In contrast, in the G2-L group, significant hindlimb postural abnormalities including external rotation of femur, internal rotation of tibia and foot, external rotation of tarsal joint, large stifle joint convergence angle, genu varum and toe-in standing were observed.Conclusion Dogs with grade 2 MPL have no bone deformities but show abnormal standing posture when the patella is luxated.
Keywords: bone deformities; computed tomography; dogs; patellar luxation; postural abnormalities